2009
DOI: 10.1186/1756-8722-2-30
|View full text |Cite
|
Sign up to set email alerts
|

Gender and ethnic differences in chronic myelogenous leukemia prognosis and treatment response: a single-institution retrospective study

Abstract: Background: In the last decade the importance of ethnicity, socio-economic and gender differences in relation to disease incidence, diagnosis, and prognosis has been realized. Differences in these areas have become a major health policy focus in the United States. Our study was undertaken to examine the demographic and clinical features of chronic myelogenous leukemia (CML) patients presenting initially at the LAC+USC Medical Center, which serves an ethnically diverse population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
17
1
3
Order By: Relevance
“…This was a substantial increase after 6 months (at which time the rates were 12% in one study and 17% in the other) 27,29 . While our response rates reported here are appreciably lower that those previously reported in randomized, controlled phase III trials (as has been shown to occur in other retrospective analyses of response rates among imatinib-treated patients 35,36 ), it is important to recognize the differences with respect to the frequency of response monitoring between real-world community practice and rigorously designed and conducted randomized trials 4,13,16,27 . While the rate of cytogenetic and/or molecular response monitoring during the first 3 months was 450%, ideally all patients should be tested in that early timeframe.…”
Section: Discussioncontrasting
confidence: 56%
“…This was a substantial increase after 6 months (at which time the rates were 12% in one study and 17% in the other) 27,29 . While our response rates reported here are appreciably lower that those previously reported in randomized, controlled phase III trials (as has been shown to occur in other retrospective analyses of response rates among imatinib-treated patients 35,36 ), it is important to recognize the differences with respect to the frequency of response monitoring between real-world community practice and rigorously designed and conducted randomized trials 4,13,16,27 . While the rate of cytogenetic and/or molecular response monitoring during the first 3 months was 450%, ideally all patients should be tested in that early timeframe.…”
Section: Discussioncontrasting
confidence: 56%
“…59 Despite presenting with a less favorable risk profile, female patients have been shown to respond better to therapy than males and resulted with a significantly better overall survival in earlier trials and at least comparable outcomes in more recent studies. 59,60 In contrast, there is emerging evidence at least in a t(8;21)-positive subgroup of pediatric patients with acute myeloid leukemia (AML), that male gender is a positive prognostic factor for survival. 61 Other studies have not shown any gender difference concerning outcome in adult AML patients.…”
Section: Myeloid Leukemiamentioning
confidence: 96%
“…The disease is more common in males. There is no clear evidence of to geographic or ethnic background that predisposes to CML; however, in the United States the incidence is slightly higher in Caucasians than in Blacks or Hispanics (Lee et al, 2009), and it exhibits a male preponderance, in South African Coloured and Black people, and African Americans in comparison to whites but the reason for this is unexplained. (Jacobs et al, 1983).…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…Interestingly both sides of the argument seem to find support. Chronic myeloid leukemia (CML) patients show worse survival for African American and Hispanics compared to Americans of European origin (Lee et al, 2009). Although the difference in ethnicity data might be argued to reflect socio-economic differences, the current advances in genomics enable the implication of particular genomic regions and genes that explain the ethnic differences in susceptibility to infectious and chronic diseases.…”
Section: Introductionmentioning
confidence: 99%